2021
DOI: 10.3390/plants11010022
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nitrogen Sources Applied by Fertigation to an Enriched Soil with Organic Compost on Growth, Mineral Nutrition, and Phytochemicals Content of Coriander (Coriandrum sativum L.) in Two Successive Harvests

Abstract: The aim of the present study was to evaluate the effects of nitrogen source applied by fertigation to an enriched soil with organic compost on plant growth, mineral nutrition, and phytochemical contents in two successive harvests in coriander. The treatments were as follows: unfertilized soil, soil enriched with organic compost, and soil enriched with organic compost to which 60 kg N ha−1 as ammonium nitrate and as ammonium sulfate applied by fertigation were added. Ammonium nitrate addition allowed to obtain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Eisa [61] found that organic additives (farmyard and chicken manure) and mineral NPK (50 and 100% of RD) resulted in the highest N, P, and K content in fennel plants. Previous studies proved that the accumulation of N, P, and K in plants in response to chemical, organic, and bio-fertilizations as reported in caraway [47], chamomile [62], collard [63], moringa [32], kale [64], and coriander [65]. Increasing the content of carbohydrates, N, P, and K in the above-ground parts of the fennel had a similar enhancing effect on fruit and EO yields.…”
Section: Discussionmentioning
confidence: 57%
“…Eisa [61] found that organic additives (farmyard and chicken manure) and mineral NPK (50 and 100% of RD) resulted in the highest N, P, and K content in fennel plants. Previous studies proved that the accumulation of N, P, and K in plants in response to chemical, organic, and bio-fertilizations as reported in caraway [47], chamomile [62], collard [63], moringa [32], kale [64], and coriander [65]. Increasing the content of carbohydrates, N, P, and K in the above-ground parts of the fennel had a similar enhancing effect on fruit and EO yields.…”
Section: Discussionmentioning
confidence: 57%
“…This finding was consistent with the heat map, which revealed a correlation coefficient of 0.9 for the TPC and FRAP parameters (Figure 9). Previous studies have reported a correlation between the TPC and antioxidant activity, as assessed by the FRAP assay [55,56]. Another noteworthy observation was the proximity of the vectors representing the FRAP and polyphenol oxidase (Figure 8).…”
Section: Discussionmentioning
confidence: 61%
“…Coriander plants must be provided with nitrogen during the growing season in order to accomplish the necessary increase in vegetative growth and quality improvement and production 79 , 80 . Moreover, N fertilization affects the accumulation of phytochemicals in the plant, including phenolic compounds, and nitrogen deficiency, which may lead to an increase in their concentration in the plant 81 .…”
Section: Discussionmentioning
confidence: 99%